Nanocrystallization of ferroelectric lithium niobate in LiNbO3-SiO2 glasses - P. Prapitpongwanich (2018)
Transparent glasses in the (100-x)LiNbO3-xSiO2system where 20 ≤ × ≤ 35, were produced by conventional melt-quenching technique. The quenched samples were amorphous as proved by X-ray diffraction (XRD) technique. Annealing of the quenched samples at temperatures ranging from 580 to 975 °C resulted in the precipitation of lithium niobate nano-crystals. Scanning electron microscopy (SEM) showed the presence of randomly oriented LiNbO3nano-crystals dispersed in a continuous glass matrix. The relative dielectric constant (εr) was in the range of 80 to 180 and increased with increasing LiNbO3concentration. The glass ceramic samples annealed at temperatures up to 600 °C are fully transparent. © 2009.